Psychological, neuroendocrine and inflammatory stress responses in women after miscarriage or stillbirth: investigating early psychobiological adaptations to potential traumatic events - Gerber, Luis; Müller, Markus M.; Oender, Alexandra; Urbanczyk, Sophia; Radermacher, Peter; Brucker, Cosima; Stein, Barbara; Waller, Christiane; Rohleder, Nicolas (Journal of Neural Transmission, 2025)
Background: Miscarriage (MC) and stillbirth (SB) can be considered as potentially traumatic events (PTE) and affect approximately 10–20% of all pregnancies. PTEs can lead to the development of post-traumatic stress disorder (PTSD). While the psychobiology of PTSD is well-understood, our knowledge on psychobiological adaptations shortly after a PTE is limited. This study aimed to shed light on early psychobiological changes associated with MC and SB. Methods: We included 25 women who had experienced a MC/SB within the previous three months and compared them with 28 healthy control women. All participants were asked to attend a study appointment, during which they participated in a socially evaluated cold-pressor test (SECPT) to induce psychosocial stress. Saliva and blood samples were collected at rest, immediately and at 20, 45 and 90 min after the SECPT. We determined salivary cortisol levels and α-amylase (sAA) activity, and plasma interleukin-6 (IL-6) concentrations. We assessed symptoms of PTSD, anxiety and depression using self-report questionnaires. Results: Women who had experienced MC or SB reported significantly more symptoms of PTSD (p < 0.001) and anxiety (p < 0.001), when compared to the control group. Despite elevated psychological distress in the MC/SB group, there were no significant differences of salivary cortisol, sAA and IL-6 levels between the two groups at rest or after SECPT induced stress. Conclusions: Despite the high psychological strain on women after MC/SB, the stress is not yet reflected at a biological level. These results highlight the complex relationship between early trauma, PTSD symptoms, and biological responses. Further research is needed to understand the long-term effects of trauma related to MC/SB, and the development of PTSD, as well as the underlying mechanisms contributing to the observed psychological and biological changes.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Biological response; Miscarriage; Post-traumatic stress disorder; Potential traumatic event; Stillbirth; Stress reactivity; Trauma